2021
DOI: 10.1002/micr.30829
|View full text |Cite
|
Sign up to set email alerts
|

Acellular nerve graft enriched with mesenchymal stem cells in the transfer of the phrenic nerve to the musculocutaneous nerve in a C5‐C6 brachial plexus avulsion in a rat model

Abstract: IntroductionPhrenic nerve transfer has been shown to achieve good nerve regeneration in brachial plexus avulsion. Acellular nerve allografts (ANAs) showed inferior results to autografts, which is why its use with mesenchymal stem cells (MSCs) is currently being studied. The aim is to study the effect of BM‐MSCs associated with ANAs in a rat model of phrenic nerve transfer to the musculocutaneous nerve in a C5‐C6 avulsion.Material and methods42 Wistar‐Lewis rats underwent a C5‐C6 lesion in the right forelimb by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Furthermore, morphological and immunohistochemical measurements demonstrated improvements, including reduction of inflammatory cell infiltration and vacuole formation in injured nerves and decreased expression of SP and IBA1 in spinal dorsal horns corresponding to BPA levels, indicating CWS as a potential therapy for reducing inflammation and pain at early stage of peripheral nerve injury. Many studies reported better functional recovery by cell transplantation, immunotherapy, or nerve transfers when other forms of therapeutic interventions were also applied for management of severe peripheral nerve injury [13][14][15][16]. The present findings evidenced the potential of CWS in enhancing sensory and motor functional recovery, in addition to modulating BPA-induced neuropathic pain.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, morphological and immunohistochemical measurements demonstrated improvements, including reduction of inflammatory cell infiltration and vacuole formation in injured nerves and decreased expression of SP and IBA1 in spinal dorsal horns corresponding to BPA levels, indicating CWS as a potential therapy for reducing inflammation and pain at early stage of peripheral nerve injury. Many studies reported better functional recovery by cell transplantation, immunotherapy, or nerve transfers when other forms of therapeutic interventions were also applied for management of severe peripheral nerve injury [13][14][15][16]. The present findings evidenced the potential of CWS in enhancing sensory and motor functional recovery, in addition to modulating BPA-induced neuropathic pain.…”
Section: Discussionsupporting
confidence: 59%
“…The group that received differentiated ADSCs showed improved compound muscle action potential and motor conduction velocity as well as histologically more neurofilament, S100, larger diameter axons, thickened myelin sheaths, and higher-density myelination [ 64 ]. Another study transferred the phrenic nerve to restore the musculocutaneous nerve in C5-C6 avulsion injury in rats but instead used bone marrow stem cells in the treatment group to seed acellular nerve grafts [ 65 ]. Interestingly, there were no differences reported between groups with acellular nerve grafts and groups where acellular nerve grafts were seeded with bone marrow stem cells (BMSCs).…”
Section: Animal Studies Utilizing Fat In Various Types Of Peripheral Surgerymentioning
confidence: 99%